2023
DOI: 10.21037/ccts-20-171
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in lung cancer screening: a narrative review

Abstract: Although when used as a lung cancer screening tool low-dose computed tomography (LDCT) has demonstrated a significant reduction in lung cancer related mortality, it is not without pitfalls. The associated high false positive rate, inability to distinguish between benign and malignant nodules, cumulative radiation exposure, and resulting patient anxiety have all demonstrated the need for adjunctive testing in lung cancer screening. Current research focuses on developing liquid biomarkers to complement imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This study did not combine with methylation of other DNAs known to be associated with lung cancer including SOX17, TAC1, HOXA7, and RASSF1A. 10 36 37 38 Lastly, in this study, a statistically significant increase in sensitivity was shown as the stage of the patients in the subgroup progressed, with 57.1% in stages I and II compared to 88% in stage III and IV of lung cancer. The sensitivity of this study increases as the stage progresses, however patients with advanced lung cancer require biopsy for chemotherapy rather than surgery.…”
Section: Discussionmentioning
confidence: 75%
“…This study did not combine with methylation of other DNAs known to be associated with lung cancer including SOX17, TAC1, HOXA7, and RASSF1A. 10 36 37 38 Lastly, in this study, a statistically significant increase in sensitivity was shown as the stage of the patients in the subgroup progressed, with 57.1% in stages I and II compared to 88% in stage III and IV of lung cancer. The sensitivity of this study increases as the stage progresses, however patients with advanced lung cancer require biopsy for chemotherapy rather than surgery.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, positive and negative predictive values are of equal importance; it is necessary to be able to discern those patients with a positive test who actually have the disease and those with a negative test who are truly disease-free [ 11 ]. The use of a risk-predictive biomarker for a disease with low prevalence requires a strong negative predictive value [ 12 ]. Furthermore, a clinically useful biomarker should be easily measurable, accurate, reproducible and inexpensive [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A neoplastic mass can be detected, at least at routine imaging screening, once it has reached a diameter of at least 0.5/1 cm [ 133 , 134 ]; however, noninvasive blood tests based on circulating tumor DNA and epigenetic traits can allow earlier diagnosis [ 135 , 136 , 137 ]. This approach has been widely implemented and validated for lung cancer as well for a review, see [ 138 , 139 , 140 , 141 , 142 ]. Notably, lung cancer marker detection can be more efficiently reached through the so-called semiconductor quantum dots (QDs), namely nanoparticles featuring stable and intense fluorescence which are now employed to expand the in vitro analysis of blood and tissue samples, as well as molecular imaging [ 143 ].…”
Section: Impact Of Micro-technologies In Cancer Medicinementioning
confidence: 99%